Bacilloscopy and polymerase chain reaction of slit-skin smears and anti-phenolic glycolipid-I serology for Hansen’s disease diagnosis - Lima, Filipe Rocha; de Paula, Natália Aparecida; Simões, Mateus Mendonça Ramos; Manso, Gabriel Martins da Costa; Albertino, Gustavo Sartori; Felisbino, Giovani Cesar; Antunes, Vanderson Mayron Granemann; Perecin, Fernanda André Martins Cruz; Westin, Andrezza Telles; Lugão, Helena Barbosa; Frade, Marco Andrey Cipriani (Frontiers in Medicine, 2022)
The bacilloscopy of the slit-skin smear (SSS) is the exclusive laboratory test associated with dermato-neurological evaluation for Hansen’s disease (HD) diagnosis; however, it is negative in the majority of PB or primary neural forms. Thus, a PCR technique involving different sequences and target genes has been performed with an aim to increase the sensitivity and specificity of M. leprae identification, especially in patients with low bacillary loads. Additionally, serological assays based on antibody response reflect infection levels and indicate that this could be a simpler, less invasive technique for estimating M. leprae exposure. Serological tests and PCR have been shown to be more sensitive and accurate than the SSS. Our study aimed to measure accuracy and performance among the SSS and PCR of dermal scrapings stored on filter paper and APGL-I serology for diagnosis in HD. A cross-sectional study analyzing the medical records (n = 345) of an HD outpatient-dermatology clinic from 2014 to 2021 was conducted. Accuracy performance parameters, correlation, and concordance were used to assess the value among the SSS, PCR, and APGL-I exams in HD. The SSS presented 24.5% sensitivity, 100% specificity, 37.4% accuracy, and the lowest negative predictive value (21.5%). The PCR assay had 41, 100, and 51% sensitivity, specificity, and accuracy, respectively. PCR and APGL-I serology increased the detection of HD cases by 16 and 20.6%, respectively. PCR was positive in 51.3% of patients when the SSS was negative. The SSS obtained moderate concordance with PCR [k-value: 0.43 (CI: 0.33–0.55)] and APGL-I [k-value: 0.41 (CI: 0.31–0.53)]. A moderate positive correlation was found between the APGL-I index and the bacillary index (r = 0.53; P < 0.0001). Thus, the use of the SSS is a low sensitivity and accuracy method due to its low performance in HD detection. The use of PCR and serological tests allows for a more sensitive and accurate diagnosis of patients.